Randomized, waitlist-controlled trial of Cordyceps sinensis mycelium culture extract (Cs4) for long COVID patients in Hong Kong - Yuanyuan Chen; Guang Chen; Cheng Zhang; Guoyi Tang; Yautuen Chan; Ning Wang; Yibin Feng (Acta Materia Medica)
We assessed Cordyceps sinensis mycelium culture extract (Cs4) for alleviating long COVID symptoms. In this randomized trial 110 participants were assigned to receive Cs4 (55 participants) or were waitlisted (55 participants) for 12 weeks. The primary outcome was the change in long COVID symptom severity at 12 weeks, as measured by the modified COVID-19 Yorkshire Rehabilitation Scale. The secondary outcomes included changes in the Brief Fatigue Inventory Form, Insomnia Severity Index, Hospital Anxiety and Depression Scale, St. George’s Respiratory Questionnaire, and the Short Form 12 health survey at 12 weeks. Participants receiving Cs4 showed improvement in long COVID symptoms compared to the waitlist control group (MD, −10.1; 95% CI, −14.1 to −6.1; P < 0.001) at 12 weeks. Cs4 recipients also experienced improvement in fatigue (MD, −8.1; 95% CI, −14.2 to −2.0; P = 0.011), insomnia (MD, −2.9; 95% CI, −4.6 to −1.2; P = 0.001), and respiratory symptoms (MD, −6.3; 95% CI, −11.4 to −1.2; P = 0.018). Cs4 also improved the quality of life (physical component MD, 7.0; 95% CI, 4.2–9.8; P < 0.001; mental component MD, 6.8; 95% CI, 2.9–10.7; P < 0.001). No severe adverse events were reported. Cs4 may be a beneficial treatment for patients with long COVID symptoms.